Role of E-Commerce in Indian Banking Sector: Exploring the impact of E-Commerce on the Indian banking sector (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The internet has changed the way things were done people purchase and sell products andservices in the previous 10 years.Indian customers' buying experiences are being transformed by ecommerce.Electronic data exchange expands to producers, retailers' traders, stock market operations,and travel bookings, among other things, resulting in increased economic growth. The word ECommercerefers to doing online commerce using computers, fax machines, and telephones. IBM wasthe first to adopt the word in 1972. The European Union and the United States conducted the initialtransactions. The establishment of the internet market in 1995 marked the start of E-Commerce in ourcountry.E-banking has grown in popularity because to its easytransactional advantages such as speed,efficiency, and accessibility are also available. The most significant benefit of e-commerce is that itbrings individuals from all corners of the globe together in a relatively short period of time. Allowindividuals to experience and access items, services, information, and other people that they may nototherwise have access to. Banks are the backbone of every country's economy, allowing for quicktransactions that were previously impossible before the advent of E-commerce. The importance of theIndian banking sector in Ecommerce is demonstrated in this study